Co-Synthesis and characterization of In2O3 and ZnO nanowires - Abrar Ismardi; Chang, Fu Dee; Hamzah, A.A; Bais, B; Salleh, M.M; Majlis, B.Y; Ille, C. Gebeshuber (Universiti Kebangsaan Malaysia, 2012)
Co-synthesis of In2O3 and ZnO nanowires (NWs) were grown on silicon and alumina substrates using vapour transport deposition method. Their morphological structures showed that the NWs were rather aligned on silicon substrate and randomly oriented on alumina substrate. The formation of NWs on silicon substrate was found to be dominated by the growth of ZnO NWs while that on alumina substrate was dominated by the growth of In2O3 NWs. The In2O3 and ZnO NWs were highly crystalline and have wurtzite structure.